Incorporating various perspectives in using instant messages in teaching programming: A critical system thinking perspective. (7th August 2022) - Manduna, Watson; Goede, Roelien; Drevin, Lynette
Abstract: In this paper, the application of instant messaging (IM) in programming training is argued to be possible and inevitable, especially in the high schools/colleges of poor communities. However, challenges in its application were noted. These challenges of utilising IM and the reluctance of the students in applying it in their programming training acted as a motivation for the study. Our aim is to use IM for a different purpose than its original intention. Critical systems heuristics was used as a multi‐methodological framework for the incorporation of various conditioned realities, where the technological pedagogical content knowledge framework was applied to incorporate the applicable technological, pedagogical, content areas. The guidelines were enhanced from knowledge gained from an action research project with trainee teachers. This iterative process demonstrates the incorporation of both theoretical and empirical context‐based perspectives into the understanding and addressing of a problem environment.